Clinical trial experience with prophylactic human papillomavirus 6/11/16/18 vaccine in young black women (2013)
Purpose: Human papillomavirus (HPV) is the causative agent of cervical cancer. Black women are disproportionally diagnosed and have higher mortality from cervical cancer in the United States. Here we describe the prophylactic efficacy and safety of a quadrivalent HPV-6/11/16/18 vaccine in black women. Methods: A total of 700 black women from Latin America, Europe, and North America (aged 16-24 years) received the vaccine or placebo in one of two studies. Analyses focused on the efficacy and safety of the vaccine. Results: Baseline rates of Chlamydia trachomatis infection and history of past pregnancy were more than twice as high in black women compared with the non-black women who were enrolled in these trials. HPV-6/11/16 or 18 DNA was detected in 18% of black women versus 14.6% in non-black women at day 1. For black women, vaccine efficacy against disease caused by HPV-6/11/16/18 was 100% for cervical intraepithelial neoplasia (0 vs. 15 cases; 95% confidence interval, 64.5%-100%) and 100% for vulvar and vaginal intraepithelial neoplasia and condylomata acuminata (0 vs. 17 cases; 95% confidence interval, 69.3%-100%). There were no serious vaccine-related adverse experiences. A similar proportion of pregnancies resulted in live births (75.8% vaccine; 72.7% placebo) and fetal loss (24.2% vaccine; 27.3% placebo). Conclusions: Prophylactic quadrivalent HPV-6/11/16/18 vaccination of young black women demonstrated high efficacy, safety, and tolerability. HPV vaccination has the potential to reduce cervical cancer-related health disparities both in the United States and around the world. © 2013 Society for Adolescent Health and Medicine. All rights reserved.